2023
DOI: 10.1136/sextrans-2022-055680
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health in Britain during the first year of the COVID-19 pandemic: cross-sectional population survey (Natsal-COVID-Wave 2) and national surveillance data

Abstract: ObjectivesTo assess sexual behaviour, and sexual and reproductive health (SRH) outcomes, after 1 year of the COVID-19 pandemic in Britain.Methods6658 participants aged 18–59 and resident in Britain completed a cross-sectional web-panel survey (Natsal-COVID-Wave 2, March-April 2021), 1 year after the first lockdown. Natsal-COVID-2 follows the Natsal-COVID-Wave 1 survey (July-August 2020) which captured impacts in the initial months. Quota-based sampling and weighting resulted in a quasi-representative populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…19 Similarly, a British study observed fewer reported abortions in the first year of the pandemic compared with data collected a decade earlier. 13 We also observed some indication of fewer abortions, particularly among women over 25 years of age. Contrastingly, we found that abortions appeared to increase somewhat among young women, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…19 Similarly, a British study observed fewer reported abortions in the first year of the pandemic compared with data collected a decade earlier. 13 We also observed some indication of fewer abortions, particularly among women over 25 years of age. Contrastingly, we found that abortions appeared to increase somewhat among young women, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 49%
“…12 Elsewhere in Europe, a British survey of 5733 participants observed fewer reported abortions in the first year of the pandemic compared with data collected a decade earlier (2010-2012). 13 Understanding the changes in birth and abortion rates is important, as changes can have significant consequences on demographic pyramids. This is even more critical in countries with an already low number of children per couple such as Sweden.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%